Estudo longitudinal dos fatores relacionados à infecção e reinfecção pelo Schistosoma mansoni em área endêmica, Minas Gerais - Leonardo Ferreira Matoso (2012)
This study aimed to evaluate the relationship between S. mansoni infection and reinfection using demographic, socioeconomic, immunological and water contact factors, in 127 individuals in Virgem das Graças, an endemic area in municipality of Ponto dos Volantes,Minas Gerais. Demographic, socioeconomic and water contact behavioral data were collected, as well as feces and blood for parasitological and serological analysis, of all individuals participating in the study between 2001 and 2009. Serum was used to evaluate specific IgE and IgG4 antibody reactivity against soluble egg (SEA) and adult worm (SWAP) antigens. The prevalence for S. mansoni infection before treatment (2001) was 59% (CI 95%= 50.38-67.72) with the geometric mean egg count (epg) of 61.05 (CI95%= 58.70 63.40). One yearafter treatment (2002), prevalence and intensity of infection reduced significantly to 16.5% (CI 95%= 9.98 23.08) and 40.6 epg (CI 95%= 37.80 43.42), respectively. In 2005, the prevalence increased to 27.6% (CI 95% = 19.68 to 35.43), but the intensity of infection remained similar to that of 2002 with 39.81 epg (CI 95% = 37.27 - 42.35). In the last year ofevaluation (2009), the prevalence remained at 26.8% (CI 95% = 18.96 to 34.57) but the intensity of infection reduced significantly to 8.78 epg (CI 95% = 6.45 to 11.11) when compared to previous years. Multivariate analysis showed that age, water contact and immunological characteristics were associated with S. mansoni infection. A higher risk of infection was observed in younger individuals (6-14 and 15-29 years) as well as in those who performed activities of fishing and crossing stream. It was shown that the increase in IgG4 anti-SEA and SWAP reactivity and the IgG4/IgE ratio against these antigens were related torisk of infection, with individuals being more susceptible to infection. Analysis of IgE anti-SEA and SWAP reactivity showed an increase over time for both infected and uninfected individuals and when stratified by age, being more significant in 2005. In regard to IgG4 anti- SEA antibodies, there was a significantly higher level of antibody reactivity in the infected individuals in all investigated years. The reactivity of IgG4 anti-SEA antibodies by age, showed a significant progressive reduction over time, except for the younger individuals (6-14 years). In relation to reinfection, we also observed a significant progressive increase in IgEanti- SEA and anti-SWAP levels over time in the group of individuals who were reinfected when compared with those who did not reinfect, and the distribution of these antibody reactivities very similar between groups. The ROC analysis showed that the IgG4anti-SEA antibody had significant power to predict infection by S. mansoni in every study points. IgG4 anti-SEA antibodies and IgG4/IgE anti-SEA ratio showed a low ability to predict reinfection, with a curve area around 66%. Our results showed that the prevalence of S. mansoni infection can not be attributed only to immunological factors. We conclude that the IgG4 anti-SEA antibody can be used as immunological monitoring biomarker to predict S.mansoni infection in endemic areas.